login
a(0)=0, a(1)=1, a(n) = -a(n-2)^2 - a(n-1)^3.
1

%I #18 Jun 16 2021 20:40:27

%S 0,1,-1,0,-1,1,-2,7,-347,41781874,-72939661777729919216033,

%T 388053169934428398618745564559557538054223536478283729487028027756061

%N a(0)=0, a(1)=1, a(n) = -a(n-2)^2 - a(n-1)^3.

%C Homogeneous cubic recurrence relation of order 2 with -1 coefficients.

%C Next term is too large to be included.

%p f:=proc(n) local i; option remember; if n=0 then 0

%p elif n=1 then 1

%p else -f(n-2)^2-f(n-1)^3; fi; end;

%p [seq(f(n),n=0..10)]; # _N. J. A. Sloane_, Jun 16 2021

%t RecurrenceTable[{a[n] == -a[n - 2]^2 - a[n - 1]^3, a[0] == 0, a[1] == 1}, a, {n, 1, 11}] (* _Michael De Vlieger_, Sep 11 2015 *)

%Y Cf. A262089.

%K sign

%O 0,7

%A _Andrew R. Reiter_, Sep 10 2015

%E Data and offset corrected by _N. J. A. Sloane_, Jun 16 2021